Business model canvas : GarNaz Sdn Bhd / Naelah Abdullah Zawawi - Zawawi, Naelah Abdullah (2020)
GarNaz Sdn Bhd provide the customers product and services such as gardening tools that will surely meet the level of customer’s satisfaction. Mostly the customer are trying so hard to find the solution to their problem. So, our customer target which is gardener as well as elderly are trying to figure out some gardening tools to settle down their messy garden problem. GarNaz Sdn Bhd offer high quality of portable plant support for the customer. GarNaz Sdn Bhd has get into marketing strategy to expand the business by looking forward a very good care of the quality of portable plant support. Futher more, this product is affordable and can be purchased by everyone with high or low income rates. There are so much to explore about the gardening tools, especially portable plant support. The management of GarNaz Sdn Bhd is Naelah Binti Abdullah Zawawi as a General Manager. She also handling the financial part of the business. The Human Resources Manager and Marketing Manager is Abdullah Zawawi Mohammed and Sunee Useng respectively. The staff is both Zomri Abdullah Zawawi and Farish Adlan Abdullah. The business plan of product as well as services is going to reach a peak if the plan are aggressively build through many good platform. The unique and attractive portable plant support will surely help them to solve the problem they faced.